Relationship of River to Salinity Well Water in Bintaran Village, Sub-District Air Salek - Ningrum, Rahayu Rohmana Vidiati; Utomo, Budi (Universitas Veteran Bangun Nusantara, 2020)
This study aims to determine the relationship of rivers to salinity of well water in Bintaran Village, Air Salek Sub-district. The research method used is quantitative descriptive. The study population was all wells in Bintaran Village, Air Salek Sub-district, with a sample of 16 samples taken from 8 wells in Bintaran Village, Air Salek Sub-district, in the morning >07.00 Am, and at noon <12.00 Pm. Data collection techniques using observation, laboratory tests, and documentation. Data analysis techniques using produck moment correlation techniques. The results showed that the relationship of the river to the salinity of well water had a significant relationship, namely the morning salt content of the value 0.794, and the day salt content of the correlation value was 0.807, the closer the well to the river the lower the salt content.